Improving Livelihood Options via Agriculture: A Case Study of Social Entrepreneurship, Kedah - K. Kuperan Viswanathan, Sabirah Sulaiman, Lim Hock Eam, (Opción, 2019)
This study explores how cumulative impact creation and multitasks holder effort make it possible to overcome the struggles of social entrepreneurship via agriculture. Out of the desire to contribute in an evidence-based and demand-driven manner to the individual and economic empowerment of women living in Lunas and its neighboring town, Kulim. The result showed that the aim of the Community Needs Assessment Process is to create an interaction and a safe discussion place between representatives of the organization and the representatives of its target groups so to gain a better understanding the challenges of the target group and their communities.